The Consequences of Unfreedom: Learning from Story Amidst a Global Climate Crisis - Robinson, Meghan (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2022)
As the world navigates the impending consequences of climate change, Canada remains one of the few countries to reject the right to a healthy environment for its citizens within the Canadian Constitution. Although Canada purports itself to be a free and democratic society, many argue that their freedoms are continually neglected by laws that continue to disregard the environment and, therefore, their right to a healthy existence. This article is an investigation into a particular word that is woven throughout Canada’s Constitution: “freedom.” It is an investigation into the conflicting understandings of the word and how these contrasting meanings have impacted Canada’s Constitution and its relationship to land. This article analyzes the history of freedom as seen through a liberal belief system and contrasts this understanding with Indigenous concepts of freedom, as told through Haisla and Nuu-chah-nulth stories. These narratives explore how the differing concepts of freedom have affected relationships with the land and the laws that govern the land. Finally, the discussion of these themes draws upon the possibility of using story within Canada’s laws to change the Constitution’s current relationship with the land in order to mitigate the potential effects of climate change. I argue that the liberal, colonialist world view is ever present in our current legal system and is in fact facilitated through the word “freedom.” Until we begin to re-story our Constitution through a diversity of understandings and world views, Canada will continue to ignore the looming ramifications of climate change.